Psikologi Pendidikan Pada Pendidikan Empati : Tinjauan Analitis - Wijayanti, Rina (Sultan Idris Journal of Psychology and Education, 2025)
This article examines the role of the philosophy of educational psychology in forming the theoretical and practical foundations for empathetic education in Indonesia as a response to contemporary social challenges, such as social polarization, low social cohesion, and increasing interpersonal conflict. The purpose of this study is to analyze the main concepts of the philosophy of educational psychology that underlie empathic education, including ontological, epistemological, and axiological dimensions, and to evaluate the implementation of empathic education in local and global contexts. The method used is the *Systematic Literature Review* (SLR) approach, by deeply examining various current academic literature, including scientific journals, books on the philosophy of educational psychology, and empirical research results from Indonesian and international contexts (Hanurawan, 2020; Gates & Curwood, 2023; Kolb, 1984). The results of the study show that empathic education requires a holistic philosophical framework, including the development of students' emotional, social, and moral perspectives. The ontological dimension examines the psychological and social realities of empathy; epistemology evaluates methods of measuring and developing empathy through empirical and narrative approaches; while axiology highlights the ethical value of empathetic education in creating an inclusive society. The study also highlights the successful implementation of empathetic education in countries such as Finland and its adaptation in Indonesia through local wisdom-based character education. This approach has proven effective in improving students' social competence and reducing social conflict. This article concludes that the philosophy of educational psychology provides an important conceptual framework in designing empathetic education that is contextual, transformative, and adaptive to Indonesia's socio-cultural dynamics.